2010
DOI: 10.1021/nn901278t
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Deposition of Au Nanoparticles in CNT Films by Chemical Bonding

Abstract: T he overall electrical, thermal, and mechanical performance of networks of overlapped and crisscrossed carbon nanotubes (CNTs) (also called buckytube paper, CNT films, etc.) is largely determined by the nature of the contact at the nodeOthat is, the intersection of overlapping CNTs. To our knowledge, there has been no work to date on selective modification of the nodes in CNT networks, and we report here on such an effort, with an eye towards improving the transparent electrode performance of such networks.Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…Therefore it was interesting to examine whether the sulfate derived from P. douarrei was the result of the sulfur amino acid decomposition during the thermic treatment, which could explain the abnormal high level of sulfates. It had been 95 reported that cysteine, methionine, glutathione and proteins are thermally decomposed, at 400°C, in various gases such as H 2 O, H 2 S, CO 2 , NO 2 , SO 2 , and N 2 O 3 [16,17]. That is why we concluded that the excessive amount of sulfate measured was not a consequence of an unusual sulfur amino acid contained in the 100 plant.…”
Section: Resultsmentioning
confidence: 55%
“…Therefore it was interesting to examine whether the sulfate derived from P. douarrei was the result of the sulfur amino acid decomposition during the thermic treatment, which could explain the abnormal high level of sulfates. It had been 95 reported that cysteine, methionine, glutathione and proteins are thermally decomposed, at 400°C, in various gases such as H 2 O, H 2 S, CO 2 , NO 2 , SO 2 , and N 2 O 3 [16,17]. That is why we concluded that the excessive amount of sulfate measured was not a consequence of an unusual sulfur amino acid contained in the 100 plant.…”
Section: Resultsmentioning
confidence: 55%
“…Those binding energies can be assigned to carbon vacancy, sp 2hybridized carbon, sp 3 -hybridized carbon, C-O and C=O, respectively. 42 These results mean that carbon atoms in the graphene could be etched, resulting in breaking the symmetry of sp 2 -hybridized and vacancy carbon atoms. As shown in the table, the area of sp 2 component decreased from 71.0 to 34.4% after etching.…”
Section: Xps Analysismentioning
confidence: 99%
“…The photographs of breast cancer tumors resistant to chemotherapy revealed their substantial reduction in size after treatment with the nanodiamonds-DOX complexes. 448,449 Other carbon nanomaterials as the fullerenes, carbon nanohorns, and carbon nanotubes (CNTs), have been used as carriers in drug delivery 450 due to their facile functionalization, [451][452][453] high carrier capacity, 454,455 high chemical stability, 456,457 and feasibility of incorporating both hydrophilic and hydrophobic substances. 458,459 However, important safety issues have been raised in the literature regarding their high toxicity.…”
Section: Nanomedicines Based On Hybrid Biomimetic Systemsmentioning
confidence: 99%